THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ROLE BREADTH SELF-EFFICACY ON ORGANIZATIONAL RESILIENCE - Amelia, Luna; Purbiyati, Yuliana Sri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This study investigate the influence of transformational leadership and role breadth self-efficacy on organizational resilience. It also investigates the role of breadth self-efficacy as a mediating variable between transformational leadership and organizational resilience. The study utilized a take a look at, with the representative or sample size insistent on based on the Krejcie et al. (1970) table, where the multitude of 100 corresponds to a sample size of 80. The sample consisted of 80 teachers and staff from Catholic high schools in Surabaya. This study employed partial least squares structural equation modeling (PLS-SEM) to test the hypothesis. The discovery indicate a significant, positive, and strong relationship between transformational leadership and role breadth self-efficacy with organizational resilience, either directly or through mediation, mediated by role breadth self-efficacy. This study has practical benefits for school principals. to understand the advantage of transformational leadership and role breadth self-efficacy in establishment organizational resilience in schools. Future research is suggested to explore the impact of transformational leadership and role breadth self-efficacy on organizational resilience in schools to supply new perception into the role of transformational leadership and role breadth self-efficacy in fostering organizational resilience.